DETERMINATION OF THE ENVIRONMENTAL FRAGILITY INDEX FOR THE GEOAPTITUDE VARIABLE AS A TOOL FOR LAND USE PLANNING. APPLICATION TO THE CANTON OF ESPARZA, PUNTARENAS, COSTA RICA. - Ramírez Granados, Pablo Ignacio (2025)
The methodological application of the Environmental Fragility Index is presented as a tool for guiding Local Environmental Planning (OAT) using the example of the Geoaptitude factor in the canton of Esparza, Puntarenas province, Costa Rica. Through the collection of desk information, processing of primary data, and local studies, the geological and geomorphological map was categorized to establish value categories for geoaptitude. By integrating hydrogeological information, slope stability, and natural hazards, geological and geomorphological maps were used for zoning through a Geographic Information System (GIS) and the development of categorized areas of environmental fragility. The application of the methodology through GIS allowed the creation of five categorized maps based on lithopetrophysical factors, external geodynamics, slope stability, hydrogeology, and natural hazards. Each map shows the relationship of Geoaptitude characteristics with their geographical location, as well as their percentage weight. The five subfactors were analyzed in relation to current land uses, and once this process was completed, they were integrated through an arithmetic process to form integrated geoaptitude. The Environmental Fragility Index based on geoaptitude allowed for zoning to establish areas with technical limitations and areas with potential for different degrees of current and future occupation.